2011
DOI: 10.1016/j.virusres.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a linear epitope on the capsid protein of classical swine fever virus

Abstract: The capsid (C) protein of Classical swine fever virus (CSFV) is proposed to play an essential role in the replication and translation of the viral RNA. In this study, a monoclonal antibody (mAb) directed against the C protein was generated with the recombinant C protein expressed in Escherichia coli as immunogen. IFA and IPMA analysis showed that the native C protein of CSFV virions was reactive to the mAb. By truncating the C protein, we identified a linear epitope recognized by the mAb, corresponding to amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Likewise, Riitho et al (20) showed that E2, NS2, NS3 and NS5A but not P7 and C proteins were highly inducers of T cell responses. However, BVDV-C protein has been shown to induce cellular and humoral immune response in mouse model ( 65) and a B cell epitope that can induce the formation of antibodies was mapped in the C protein of BVDV (66) and other pestiviruses (67). The main inducers of antibody response against BVDV were reported to be the E2 and NS2-3 proteins and to a lesser extent E1 and Erns glycoproteins (8,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Riitho et al (20) showed that E2, NS2, NS3 and NS5A but not P7 and C proteins were highly inducers of T cell responses. However, BVDV-C protein has been shown to induce cellular and humoral immune response in mouse model ( 65) and a B cell epitope that can induce the formation of antibodies was mapped in the C protein of BVDV (66) and other pestiviruses (67). The main inducers of antibody response against BVDV were reported to be the E2 and NS2-3 proteins and to a lesser extent E1 and Erns glycoproteins (8,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…The CSFV-positive cells were proliferated further with continuous passages. At the tenth passage, the viral titers were determined by IFA using a monoclonal antibody (mAb) against the E2 protein of CSFV, as described previously [ 15 ]. In this research, FITC labeled E2 protein was purchased from MEDIAN Diagnostics Company in Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of B-cell epitopes are discontinuous in nature, but difficulties in the design of such epitopes have led to an emphasis on the identification of linear B-cell epitopes. Monoclonal antibodies (mAbs) are used widely as powerful tools for identifying linear epitopes, or for mimicking the epitopes of a variety of infectious agents (Deng et al, 2007;Kaverin et al, 2007;Zhang et al, 2011). In this study, we prepared mAbs against the N protein of IBV strain tl/CH/LDT3/03I and used them to screen for linear B-cell epitopes.…”
Section: Introductionmentioning
confidence: 99%